2021
DOI: 10.3390/microorganisms9051099
|View full text |Cite
|
Sign up to set email alerts
|

Keystone Taxa Lactiplantibacillus and Lacticaseibacillus Directly Improve the Ensiling Performance and Microflora Profile in Co-Ensiling Cabbage Byproduct and Rice Straw

Abstract: Ensiling has been widely applied to cope with agricultural solid waste to achieve organic waste valorization and relieve environmental pressure and feedstuff shortage. In this study, co-ensiling of cabbage leaf byproduct and rice straw was performed with inoculation of Lactiplantibacillusplantarum (LP) to investigate the effects of inoculation on ensiling performance and microflora profiles. Compared to the control, LP inoculation preserved more dry matter (DM) content (283.4 versus 270.9 g·kg−1 fresh matter (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Clearly, specific LAB inoculants have their unique functions. For instance, as a homofermentative LAB, Pediococcus acidilactici occupies a dominant position during the initial period of fermentation, resulting in the production of lactic acid to inhibit spoilage organisms ( 14 ), and as a functional genus of LAB in silage, Lacticaseibacillus can also directly restrain the growth of undesirable microorganisms ( 15 ). In addition, Lactiplantibacillus , one of the most commonly used inoculants, can rapidly produce lactic acid and lower the pH in forage fermentation, and Lentilactobacillus can enhance the aerobic stability of various forages ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, specific LAB inoculants have their unique functions. For instance, as a homofermentative LAB, Pediococcus acidilactici occupies a dominant position during the initial period of fermentation, resulting in the production of lactic acid to inhibit spoilage organisms ( 14 ), and as a functional genus of LAB in silage, Lacticaseibacillus can also directly restrain the growth of undesirable microorganisms ( 15 ). In addition, Lactiplantibacillus , one of the most commonly used inoculants, can rapidly produce lactic acid and lower the pH in forage fermentation, and Lentilactobacillus can enhance the aerobic stability of various forages ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of Sesbania cannabina in the silage industry is limited because of its low water-soluble carbohydrate (WSC) content (less than 5% DM) and high buffer capacity. On the other hand, coensiling is a common practice to improve fermentation quality and enhance the stability of the fermentation system ( 7 , 8 ). Numerous studies have reported the benefits of coensiling of sweet sorghum [ Sorghum dochna (Forssk.)…”
Section: Introductionmentioning
confidence: 99%
“…It is essential for plant growth and food and feeds production since N2 is required for the cell production of enzymes, proteins, photosynthesis, Chromosomes, and RNA. To supply legumes with nitrogen, rhizobia bacteria use nitrogenase, an enzyme that converts N2 from the atmosphere into nitrate [28,29]. The physiological nitrification in (BNF) process is responsible for 65 percent of the nitrogen now used in agriculture and will continue to play important role in future sustainable crop production systems.…”
Section: N2 Fixation Symbiosismentioning
confidence: 99%